Elaboration of the Sinden Technique with Mime in the Creation of Merajut Dimensi Masa - Wiflihani Wiflihani; Frisdo Ekardo (Gondang: Jurnal Seni dan Budaya, 2023)
Merajut Dimensi Masa is a theatrical performance that is the result of elaboration of the sinden technique with pantomime motion techniques. The researcher initiated a musical theater that uses Mime Gestures as a concept for creating acting in the work. This has implications for an actor to study acting, music, and pantomime. The concept of this show elevates the spirit of the Javanese Koeli Kontrak in North Sumatra as the main story idea and theme in Merajut Dimensi Masa. The method used in this research is a qualitative research method. In collecting data using observation techniques, documentation, in-depth interviews and followed by interactive analysis. The stages of the training that the researchers carried out revolved around body exercises, vocal exercises, singing, sinden and pantomime exercises. So that through this systematic work, the concept of singing theater was born using mime as a concept of acting in the medium of performing arts. This research also seeks to offer new ideas in dramaturgical acting to create dramatic elements through the arts of singing and pantomime.